Pembelajaran Menulis Teks Anekdot melalui Project Based Learning: (Studi Tindakan Kelas Dua Siklus) - Fauzi Sabadri; Laili Amalia; Ria Kasanova (Simpati, 2026)
The teaching of anecdotal text writing to Year 8 students at SMP Mutiara Sokobanah faced several challenges, including limited idea development, low engagement among some students, suboptimal distribution of responsibilities within groups, and the need for more intensive teacher guidance throughout the writing process. This study aimed to analyse the implementation of Project-Based Learning (PjBL), describe changes in student engagement and responses, and examine the development of mastery in anecdotal text writing through cyclical improvements to classroom actions. The study employed a two-cycle classroom action research design involving 18 students. Data were collected through observations, interviews, writing tests, questionnaires, and documentation and were analysed using quantitative and qualitative descriptive methods. The findings showed that 11 of 18 students (61.11%) achieved the minimum mastery criterion in Cycle I, increasing to 17 of 18 students (94.44%) in Cycle II. Observations indicated positive changes in student engagement, participation in discussions, confidence in expressing ideas, distribution of responsibilities, and project completion. Students’ responses, reported descriptively, also indicated positive acceptance of project-based learning. Improvements in the learning process and mastery outcomes in Cycle II occurred alongside refinements based on reflection on Cycle I, including more intensive teacher guidance and feedback, more varied stimuli and model texts, clearer learning instructions, and better organisation of group work. The findings provide contextual evidence that the contribution of PjBL to anecdotal text writing instruction lies in the quality of its implementation and cyclical pedagogical improvement through reflection, scaffolding, feedback, and project organisation responsive to students’ learning needs.